2017
DOI: 10.1186/s13019-017-0674-5
|View full text |Cite
|
Sign up to set email alerts
|

Postcardiotomy VA-ECMO for refractory cardiogenic shock

Abstract: Postcardiotomy cardiogenic shock (PCCS) is a rare but catastrophic syndrome that can occur following separation from cardiopulmonary bypass or at any time during the immediate postoperative course. The management of PCCS varies between clinicians, institutions and countries. The available evidence to guide this practice is limited. In their systematic review and meta-analysis, Khorsandi and colleagues report a synthesis of case-series pertinent to the use of venoarterial extracorporeal membrane oxygenation (VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…7,8 Noncardiac complications are associated with ECMO support, and the incidence of such complications increases with the duration of ECMO support. 2,3,[5][6][7][8] It is possible that earlier institution of MT following IRI may lead to even shorter duration of ECMO support and thus improved mortality. In fact, in the setting of IRI, cellular changes triggered by myocardial ischemia, and exacerbated by reperfusion, lead to permanent compromise in myocardial function and cell viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Noncardiac complications are associated with ECMO support, and the incidence of such complications increases with the duration of ECMO support. 2,3,[5][6][7][8] It is possible that earlier institution of MT following IRI may lead to even shorter duration of ECMO support and thus improved mortality. In fact, in the setting of IRI, cellular changes triggered by myocardial ischemia, and exacerbated by reperfusion, lead to permanent compromise in myocardial function and cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical outcomes in pediatric patients with postcardiotomy cardiogenic shock resulting from IRI remain poor, with the highest mortality rates or need for orthotopic heart transplantation (OHT) reported among patients requiring ECMO support. [1][2][3][4][5][6][7][8] We have previously demonstrated that intramyocardial transplantation of autologous mitochondria isolated from nonischemic skeletal muscle (ie, mitochondrial transplantation [MT]) is safe and is associated with recovery of myocardial function and improved cell viability in preclinical models of IRI. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Based on these initial results, we performed a pilot study to assess the effect of MT in a cohort of pediatric patients undergoing ECMO support for cardiogenic shock secondary to IRI after cardiac surgery 11 compared with a matched cohort of patients who did not receive MT.…”
Section: Central Messagementioning
confidence: 99%
“…It is possible to reduce it up to 40 % with VA-ECMO implantation [Nwozuzu 2016;Guihaire 2017]. There are still no concrete guidelines for implantation time and VA-ECMO management [Charlesworth 2017]. Many studies were designed to identify risk factors for mortality [Rastan 2010;Biancari 2018;Wang 2018].…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 20 Acute complications of AMI such as ventricular septal rupture, 21 LV free wall rupture, acute mitral regurgitation, and cardiac tamponade account for the other ischemic etiologies of cardiogenic shock. 3 Other non-ischemic etiologies 22 include valvular regurgitation and stenosis, aortic dissection, primary LV dysfunction like acute decompensated heart failure, post cardiotomy syndromes, 23 takotsubo cardiomyopathy, 24 , 25 myocarditis, infiltrative disorders 26 (like sarcoidosis, amyloidosis, hemochromatosis), acute tachyarrhythmia and bradyarrhythmia, 27 infective endocarditis, pericarditis and constrictive pericarditis. 28 Rare causes include severe hypertrophic obstructive cardiomyopathy, peri, and post-partum cardiomyopathy.…”
Section: Etiologymentioning
confidence: 99%